2018
DOI: 10.1002/jms.4307
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonication‐assisted spray ionization‐based micro‐reactors for online monitoring of fast chemical reactions by mass spectrometry

Abstract: Microfluidics can be used to handle relatively small volumes of samples and to conduct reactions in microliter‐sized volumes. Electrospray ionization can couple microfluidics with mass spectrometry (MS) to monitor chemical reactions online. However, fabricating microfluidic chips is time‐consuming. We herein propose the use of a micro‐reactor that is sustained by two capillaries and an ultrasonicator. The inlets of the capillaries were individually immersed to two different sample vials that were subjected to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
(78 reference statements)
0
8
0
Order By: Relevance
“…Analytical mass spectrometry is a complex term, referring to three major research tasks of qualitative , quantitative , and structural analyses . However, pursuing the exact chemometrics (|r| = 1) is a challenging analytical task [ 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. Among theoretical model equations that are particularly relevant are those producing exact method performance.…”
Section: Introductionmentioning
confidence: 99%
“…Analytical mass spectrometry is a complex term, referring to three major research tasks of qualitative , quantitative , and structural analyses . However, pursuing the exact chemometrics (|r| = 1) is a challenging analytical task [ 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. Among theoretical model equations that are particularly relevant are those producing exact method performance.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Chen and coworkers described a ultrasound-assisted spray ionization (UASI) for the complementary detection of biomacromolecules without post-ionization such as sonic spray ionization (SSI) (Chen et al, 2010b). Low-frequency ultrasound could support the desorption of analytes without chemical changes in molecules (Chen et al, 2010a(Chen et al, , 2019a and are more suitable for the online monitoring of reactions performed under ultrasonication (Lin et al, 2014). Many excellent ion sources, such as VUV lamp-based chargetransfer ionization (VUV lamp-based CTI) (Hua et al, 2011), gravitational sampling electrospray ionization (GS-ESI) (Hsu et al, 2014) and contactless atmospheric pressure ionization (C-API-MS) (Hsieh et al, 2012), have recently been reported for online reaction monitoring, which would also be prospective for further developments.…”
Section: Homogeneous Reactionsmentioning
confidence: 99%
“…[23][24][25][26]35,42 These approaches are called as field-induced 21 or contactless ionization methods. [23][24][25][26][27][29][30][31][35][36][37][38][39][40]42 For example, when a small piece of insulating fiber 23 or one piece of electric conductive material 25,26,39 was placed close to the metal inlet of the mass spectrometer, which was applied with a high voltage, volatiles or semivolatiles derived from the solid sample deposit on the fiber could be readily ionized and detected by the mass spectrometer. Corona discharge-like processes occur to initiate the ionization of volatiles and semivolatiles derived from the sample, although no direct electric contact was applied on the ionization emitter.…”
Section: ■ Introductionmentioning
confidence: 99%